(untitled) (Islas, 2025)
Introduction: The management of tourism activity is essential for local development in its socio-cultural dimension, by promoting the enhancement of the identity and cultural heritage of the communities. Integrated and culture-oriented management not only improves the quality of life of the population, but also reinforces the sense of belonging and preserves values. Methods: Theoretical and empirical methods were used that allowed the design of a model and procedure focused on the integrated management of tourism activity, led by the government. This model prioritizes cultural conservation and the strengthening of local strategies, integrating economic, social and cultural dimensions. Results: The positive impact on tourism performance is highlighted, aligned with multilevel public policies that contribute to the protection and revaluation of cultural heritage. A significant case is that of the Plaza de La Marqueta Cultural Complex, where economic diversification, innovation and entrepreneurship are encouraged, always from a cultural approach that promotes sustainability and community roots. Conclusions: The results of this article corroborate the importance of government leadership in the integration of tourism processes with local development, ensuring that it contributes to the preservation of cultural heritage and the strengthening of cultural identity as an engine of progress and social cohesion.